ANALYSIS OF ROCK LOAD HEIGHT FACTORS USING THREE DIMENSIONAL FINITE ELEMENT METHODS - Christian Pasaribu, Boris
In the design of an underground mine, it is necessary to analyze the physica; properties and mechanical properties of the rock. The analysis is based on the Rock Mass Rating (RMR) classification system. The RMR classification can determine the method of excavation to be used during mining operations. Rocks excavated underground causes the stress conditions in the soil and rock masses to remain unchanged, resulting in dimensional changes and tunnel collapse. This study aims to analyze the height of the collapse factor using RockScience 3 (RS3) software by implementing the finite element method in the analysis process. The analysis was performed using the mean value of each RMR class. From this value, we get the parameters to make the tunnel model to be tested. The tunnel is modeled in a horseshoe shape with a width and height of 5 meters with a weighting unit of 0.027 MN / m3. Material parameters are calculated using the theoretical formula and the Rock Mass Rating (RMR) table. The results of the study showed that the collapse for class 1 rock was 0.5 meters, class 2 was 1.7 meters, class 3 was 4.3 meters, class 4 was 15.8 meters and class 5 was more than 50 meters. There are considerable errors for rocks of progressively poor quality due to many factors. The factors affecting the height of the collapse are the dimensions of the tunnel, the excavation tunnel, the depth, the working stress and the rock condition